Building Climate Resilient Agriculture in Caribbean Countries: Saint Lucia - Hayman, Alicia (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
The agriculture sector in Saint Lucia is primarily small-scale and rain-fed, with limited use of modern technology. Agriculture has not been prioritized in Saint Lucia’s NDCs due to challenges such as limited data availability, resource constraints, inadequate support services, and insufficient financing. However, opportunities for building climate resilient agriculture (CRA) and enhancing climate ambition in NDCs exist through initiatives such as promoting agroforestry, using biodigesters to reduce emissions from livestock, and using solar energy for irrigation. Additional economic and social feasibility analyses are recommended, along with GHG inventory profiling, to assess opportunities for reducing emissions from the sector. Other measures beyond the farm gate and adaptation actions with mitigation co-benefits can also be explored.